2006
DOI: 10.1243/09544100jaero71
|View full text |Cite
|
Sign up to set email alerts
|

Continuing evolution of aerodynamic concept development using collaborative numerical and experimental evaluations

Abstract: Traditionally, computational predictions and experimental evaluations of aerodynamic concepts have been conducted separately, with little collaboration other than post priori comparisons of results. This has led to distrust and even antagonism between the computational and the experimental communities. These difficulties probably began when early computational fluid dynamic practitioners boasted that wind tunnels would become sec ondary in aerodynamic concept development within a few short years, a prediction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…They used PIV measurements to quantify the unsteadiness of the wake of the airfoil and found that measurements could not be repeated to desirable levels from one test to another. While this should not keep researchers from performing wind tunnel tests, it does point to the benefits of conducting integrated ex perimental/computational research [7], so that the strengths of each approach can be fortified and the weaknesses of each ap proach can be reduced.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…They used PIV measurements to quantify the unsteadiness of the wake of the airfoil and found that measurements could not be repeated to desirable levels from one test to another. While this should not keep researchers from performing wind tunnel tests, it does point to the benefits of conducting integrated ex perimental/computational research [7], so that the strengths of each approach can be fortified and the weaknesses of each ap proach can be reduced.…”
Section: Numerical Resultsmentioning
confidence: 99%
“…CFD simulations provide a vast array of relatively dense data, whereas wind tunnel experiments provide smaller sets of sparsely arranged data, but include the direct measurement of global variables such as lift, drag, or pitching moment. Thence, significant gains can be achieved if both data sources can be combined to provide a more complete picture of the flow field [66,67].…”
Section: Computational Techniquesmentioning
confidence: 99%